Intra-middle eastern trade: why is it so low? - Askari, Hossein; Atie, Rana; Khouri, Nicolas (PSL Quarterly Review, 2012)
The Middle East has one of the highest ratios of exports to GDP in the world, yet intra-regional trade level is one of the lowest. Intra-Middle Eastern trade is examined in detail to assess the reasons for the low level of regional trade and to recommend policies for promoting trade within the area. JEL Codes: F13, F14, O19